Effect of Self-Regulation Program on Bodyweight among Overweight and Obese Working Age Group in Nabon District, Nakhon Si Thamarat Province - วิโรจน์ ธนภรณ์; เตบเส็น พนิดา; สุวรรณคง ดุษณีย์; บุญรอด ตั้ม; ชินสีห์ ชำนาญ (Journal of Health Science of Thailand, 2024)
This quasi-experimental research aimed to investigate the effect of self-regulation program on bodyweight among 78 overweight and obese working age group in Nabon district, Nakhon Si Thammarat province. They were randomly sampling into experimental and control groups; 39 each. The experimental group received eight-weeks self-regulation program and the control group followed normal lifestyle. The research tools consisted of questionnaire for general information, food consumption, exercise and emotional management behavior. Data were analyzed using descriptive and inferential statistics. It showed that when comparing within experimental group, bodyweight and BMI had reduced after the experiment. Food consumption, exercise and emotional management behaviors showed statistically significant improvement compared to those before the program (p<0.001). Food consumption and exercise behaviors among control groups were statistically improved (p<0.001) whereas bodyweight, BMI and exercise behaviors remained no change. When matching between experimental and control group prior to experiment, there was no significant difference in all aspects. However, bodyweight and BMI of experimental group had significantly reduced compared to control group after the experiment (p<0.001). Food consumption, exercise and emotional control behaviors were better than those in the control group (p<0.001). Thus, public health workers and relevant authorities could apply self-regulation program for health promotion among working age population who are overweight and obese. This could help them to maintain normal weight and practice good health behaviors which reduce the incidence of diseases and complications.